Penerapan Pembelajaran Berdiferensiasi pada IPAS Materi Bagian- Bagian pada Tumbuhan Klasifikasi Tulang Daun di Sekolah Dasar: Application of Differentiated Learning in Science on the Material of Plant Parts, Leaf Vine Classification in Elementary Schools - Rizkina, Amalia (Anterior Jurnal, 2025)
This research aims to determine the application of learning using differentiated learning in science subjects, especially in the material of practicing the plant parts of leaf bone classification in elementary schools for grade IV students at SDN Telaga Biru 1 Banjarmasin. Information was obtained through observation and interview interactions between teachers and students. This research method is qualitative research. This research applies an assessment method in the form of a case study. The focus of the research is learning using a differentiated learning model in natural and social science lessons, especially regarding the parts of plants. The case study chosen in differentiated learning refers to a school that is the focus of the research. The results of this research are that differentiated learning can accommodate students in learning activities according to students' interests in studying the material. Differentiated learning outcomes through various interests and activities in learning each student can obtain and achieve learning goals.